Analisis Pengaruh Weton di Desa Pakunden dalam Pernikahan Menurut Teori Strukturalisme Lévi-Strauss - Nimas Ayu Jihan 'Aatika; Nadya Artika Maulani; Muhammad Jazil Rifqi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Javanese people's beliefs are very attachedto the traditions and culture of the ancestors, oneof which is about the marriage weton.The purpose of this research is to find out thecommunity's response to date regarding the weton tradition. About the weton tradition and find out what factors cause Javanese people to be unable to escape from the tradition and then analyzed byJavanese society cannot be separated from this tradition and then analyzed using the Lévi-Strauss using the theory of Lévi-Strauss Structuralism, in Lévi-Strauss theory is also known to attach a certain structure to symptoms. Theory is also known to attach a certain structure to the symptoms it faces.Of course this is very sustainable with the concept of weton in Javanese society. Weton concept that exists in Javanese society. This research uses qualitative research methodsField Research qualitative research method where the data obtained does notrequire in-depth knowledge related to the literature, but rather by interviewinginterviews with several local residents, namely Pakunden Ponorogo Village. The resultsof this research shows that 1). Pakunden community still holdsThe Pakunden community still upholds weton calculations for marriage, 2). Factors that cause people to believe in weton calculations, among others, due to the influence of family and culture, the influence of fanaticism, and the influence of religion.and culture, the influence of fanaticism, and personal experience, 3). Obtained from weton calculations in marriage carried out by the Pakunden community when viewed from the perspective of thePakunden community when viewed from the perspective of Lévi-Strauss 's structuralism theory, namely as an effort to avoid misfortune or disaster in marriageis considered a mere myth wrapped in tradition.